1982
DOI: 10.1021/ja00383a004
|View full text |Cite
|
Sign up to set email alerts
|

Laser photoelectron spectrometry of Ni(CO)n-, n = 1-3

Abstract: Photoelectron spectra of the negative ions Ni(CO)"-, = 1-3, obtained with a fixed-frequency argon-ion laser operating at 488 nm are reported. The spectra provide the electron affinities for this series, EA[Ni(CO)] = 0.804 ± 0.012 eV, EA[Ni(CO)2] = 0.643 ± 0.014 eV, and EA[Ni(CO)3] = 1.077 ± 0.013 eV. The symmetric C-0 vibrational frequencies for the neutral complexes are obtained from the spectra. Metal-carbonyl bond strengths for the neutral carbonyls, Ni(CO)", = 1-4, are derived from these and other data. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
92
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(108 citation statements)
references
References 3 publications
15
92
0
Order By: Relevance
“…Moreover, the terminal CO group binds more tightly to iron than to nickel as reflected implicitly by the shorter Fe-CO distance in 1-2 than the Ni-CO distance in 1-3 in both the singlet and triplet states. A similar trend is noted in comparing the first metal carbonyl dissociation energies of 41 Ϯ 1 kcal/mol [47,48] in Fe(CO) 5 vs. 25 Ϯ 2 kcal/ mol [49] in Ni(CO) 4 . The 1-2Q quintet state structure is special ( Figure 4) with a non-linear Ni-Fe-CO unit (121.8°) in contrast to 1-2S and 1-2T with linear Ni-Fe-CO units.…”
Section: Cp 2 Feni(co)supporting
confidence: 75%
“…Moreover, the terminal CO group binds more tightly to iron than to nickel as reflected implicitly by the shorter Fe-CO distance in 1-2 than the Ni-CO distance in 1-3 in both the singlet and triplet states. A similar trend is noted in comparing the first metal carbonyl dissociation energies of 41 Ϯ 1 kcal/mol [47,48] in Fe(CO) 5 vs. 25 Ϯ 2 kcal/ mol [49] in Ni(CO) 4 . The 1-2Q quintet state structure is special ( Figure 4) with a non-linear Ni-Fe-CO unit (121.8°) in contrast to 1-2S and 1-2T with linear Ni-Fe-CO units.…”
Section: Cp 2 Feni(co)supporting
confidence: 75%
“…Complexes with the ligand CO have been prepared with all transition metal elements, but the heavier analogues of homoleptical Ni(CO) 4 with elements Pd and Pt could not become isolated so far. Pd(CO) 4 and Pt(CO) 4 have only been identified in argon matrices below 10 K [2]. The instability of the compounds comes from the weak metal-carbonyl bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The instability of the compounds comes from the weak metal-carbonyl bonds. Quantum chemical studies have shown that the first bond dissociation energies (BDE) of Pd(CO) 4 and Pt(CO) 4 are very low (Ͻ 15 kcal/mol) [3]. The experimental value of the first BDE of Ni(CO) 4 is D o ϭ 25 ± 2 kcal/mol [4].…”
Section: Introductionmentioning
confidence: 99%
“…The ADE is determined to be 1.023  0.124 eV, which is in agreement with the value of 1.077  0.013 eV reported previously. 27 The vibrational frequency of Ni(CO) 3 is estimated to be 2030  320 cm -1 (Table 2), characteristic of C-O stretch, which is close to the matrix IR measurement (Table 5 2). When the second solvated H 2 O molecule is added, the VDE of Ni(CO) 3 (Table 1), respectively, which gives the ADE of 1.647  0.092 and 1.736  0.088 eV.…”
Section: Photoelectron Spectroscopymentioning
confidence: 91%